MENILAI EFISIENSI TEKNIS BELANJA PEMERINTAH TERHADAP PENDAPATAN ASLI DAERAH: STUDI KASUS WILAYAH SUMATERA MENGGUNAKAN PENDEKATAN DATA ENVELOPMENT ANALYSIS - Syaifullah, Ahmad; Mardalena; Nugraha Pratama; Rasyida Pertiwi (Universitas Islam Negeri Alauddin Makassar, 2026)
Purpose: This study aims to assess the technical efficiency of government expenditure in generating Local Own-Source Revenue across the Sumatera region within the framework of fiscal decentralization. Methods: This study applies a quantitative approach using Data Envelopment Analysis (DEA) with the Variable Returns to Scale (VRS) model. The input variables consist of operational expenditure, capital expenditure, unexpected expenditure, and transfer expenditure, whereas Local Own-Source Revenue is employed as the output variable. Findings: The results indicate that Bengkulu, Riau Islands, Lampung, South Sumatera, and North Sumatera achieved technical efficiency. Meanwhile, Aceh, Jambi, Bangka Belitung Islands, Riau, and West Sumatera experienced inefficiency in utilizing regional government expenditure. Research Implications: The findings provide policy insights for improving budget allocation through expenditure optimization, reduction strategies, and efficiency benchmarking among provinces. Originality: This study contributes empirical evidence on regional expenditure efficiency by examining the relationship between government spending composition and revenue generation performance in the Sumatera region.